Prevalence of Primary Aldosteronism in Hypertensive Subjects with Hyperglycemia. (May 2013) - Li, Nanfang; Wang, Menghui; Wang, Hongmei; Zhang, Delian; Wang, Xinling; Zu, Feiya; Chang, Guijuan; Zhou, Keming
<x xml:space="preserve">Abstract</x> The aim of this study was to examine the prevalence of primary aldosteronism (PA) in hypertensive patients with hyperglycemia. Two hundred and thirty-two hypertensive patients with hyperglycemia were screened for PA. Fifty-four subjects with an aldosterone/rennin activity ratio >20 ng/dL per ng/mL/hour underwent a saline loading test. Primary aldosteronism was present in 22.4% of patients with a plasma aldosterone concentration >5 ng/dL and 11.6% of those with plasma aldosterone concentrations >10 ng/dL. There were 14.0%–23.0% patients with PA in the diabetes mellitus group, 2.3%–23.3% in the impaired glucose tolerance group, and 9.1% in the impaired fasting glucose group. Primary aldosteronism is common in hypertensive individuals with hyperglycemia.